We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
129
2
avatar+1112 

How do I use the addition method to solve this?

 

 

4x - y = 3

 

2x + 3y = 19 

 Apr 30, 2019
 #1
avatar+74 
0

By addition method, it is the same thing as elimination, which is what it is officially called.

 

 

Elimination:

So we can mulitply the bottom equation by 2 so that we can then cancle out the "x's" later on

(2x+3y=19)*2

4x+6y=38

Now we have the two equations

 

4x-y=3 , 4x+6y=38

We can then subtract these two equations to cancel out the "x"

4x-y-(4x+6y)=3-38

-y-6y=-35

-5y=-35

5y=35

y=7

So now we have figured out our y value is 7, and we can substitute it into our equation to get our "x" value now.

4x-7=3

4x=10

x=5/2 or 2.5 

 Apr 30, 2019
 #2
avatar+104756 
0

Multiply the first equation by  3  ⇒   12x -3y   =  9

Add this to the second equation and we get

 

14x = 28      divide both sides by 14

x = 2

 

And using  4(2) - y  = 3   ⇒   8 - y  = 3 ⇒    y  = 5

 

So

 

{x, y }  = { 2 , 5 }

 

 

cool cool cool

 Apr 30, 2019

28 Online Users

avatar
avatar
avatar
avatar